x2y2(y - x) + y2z2(z - y) - z2x2(z - x)
= x2y3 - x3y2 + y2z3 - y3z2 - z2x2(z - x)
= (y2z3 - x3y2) - (y3z2 - x2y3) - z2x2(z - x)
= y2(z3 - x3) - y3(z2 - x2) - z2x2(z - x)
= y2(z - x)(z2 + xz + x2) - y3(z - x)(z + x) - z2x2(z - x)
= (z - x)[ y2(z2 + xz + x2) - y3(z + x) - z2x2 ]
= (z - x)(y2z2 + xy2z + x2y2 - y3z - y3x - z2x2)
= (z - x)[ (y2z2 - y3z) - (x2z2 - x2y2) + (xy2z - xy3)
= (z - x)[ y2z(z - y) - x2(z2 - y2) + xy2(z - y) ]
= (z - x)[ y2z(z - y) - x2(z - y)(z + y) + xy2(z - y) ]
= (z - x)(z - y)[ y2z - x2(z + y) + xy2 ]
= (z - x)(z - y)(y2z - x2z - x2y + xy2)
= (z - x)(z - y)[ (y2z - x2z) - (x2y - xy2) ]
= (z - x)(z - y)[ z(y2 - x2) - xy(x - y) ]
= (z - x)(z - y)[ z(y - x)(y + x) + xy(y - x) ]
= (z - x)(z - y)(y - x)[ z(y + x) + xy ]
= (z - x)(z - y)( y - x)( yz + xz + xy)